Peran Zakat dalam Pengentasan Kemiskinan di Indonesia - Wardani, Lale Ajeng Khalifatun (Ikatan Da'i Indonesia, 2024)
Zakat, as an obligation that must be fulfilled by Muslims, plays a significant role in reducing poverty in Indonesia. In a Muslim-majority country like Indonesia, the potential of zakat is huge, but the level of zakat collection is still low. Improvement in the management of zakat is needed to enlarge its contribution in overcoming poverty. The method applied is a qualitative approach with library research to collect data from various sources such as books, journals, and other written materials. Poverty in Indonesia is a complex problem and is not only related to minimal income, but also related to the affordability of basic services. Through the principle of zakat, wealth can be distributed from the wealthy to the deserving groups, including the poor and dhuafa.